Q: What is 2a - 5 equals -3a?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

a + a + a - 2a = 3a - 2a = a

depends what 'a' =

2a - 4y = 3a - 8a - 5y 7a = -ya = -(y/7)

2a + 7b = -13a - 7b = -5The system of equations can be solved by elimination:2a + 3a = -65a = -6a = -6/5substitute the value of a in any of the two original equations to find the value of b:2(-6/5) + 7b = -1-12/5 + 1 = -7b-7/5 = -7bb= 1/5

(3a+4)/12 - (5/3) = (2a-1)/2Multiply each side by 12:(3a+4) - (20) = 6 (2a-1)Eliminate the parentheses:3a + 4 - 20 = 12a -63a -16 = 12a -6Add 6 to each side:3a -10 = 12aSubtract 3a from each side:-10 = 9aDivide each side by 9:-10/9 = a

Related questions

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

a + a + a - 2a = 3a - 2a = a

3a x 2a =24

2a + 3a + 4 = 5a + 4

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

depends what 'a' =

1

2a - 4y = 3a - 8a - 5y 7a = -ya = -(y/7)

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2

3a-2a = 1

The value of a is -7

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)